First Manic Episode in a 55-Year-Old Man After Initiation of Aripiprazole - Donohue, Andrew (Matrix Medical Communications, 2010)
Aripiprazole is a novel antipsychotic medication that is used to treat a number of psychiatric conditions, including schizophrenia, bipolar disorder, and major depressive disorder. Although not specifically indicated for this, novel antipsychotics including aripiprazole are also used for treatment of obsessive compulsive disorder. The following case involves a 55-year-old man with refractory obsessive compulsive disorder who developed his first manic episode after taking aripiprazole. The author reviews other cases of aripiprazole-induced mania and discusses the possible pharmacodynamic mechanisms of this reaction.